Analisis Media Statement Kasus Lion Air Penerbangan Jt-610 Boeing 737 Max 8 Dengan Pendekatan Storytelling Michael L. Kent - Prihantoro, Danang Mandala; Wulandari, Maulina Pia; Nasution, Zulkarnain (Universitas Djuanda Bogor, 2024)
The focus of this study is on how Lion Air managed crisis communication following the Boeing 737 MAX 8 crash of Flight JT-610. The research delves into the use of storytelling in media statements as a strategy for crisis communication during the aftermath of the crash. It outlines Lion Air's goals in sharing information and engaging with the public and media in the midst of this crisis. The study utilizes a qualitative text analysis to scrutinize three specific media statements released during the crisis. By applying Michael L. Kent's storytelling elements, the analysis of the media statements concentrates on factors like emplotment, narrative theory, identification, form, and masterplots. The selected statements cover the immediate aftermath of the crash on October 29, 2018; a subsequent statement on March 13, 2019, addressing broader safety concerns surrounding the Boeing 737 MAX 8; and a final statement on October 26, 2019, summarizing findings from the National Transportation Safety Committee's investigation. The research findings suggest that employing storytelling through straightforward text in media statements, incorporating credible character depiction, structured narrative, empathy, and compelling storytelling, can notably influence an organization's reputation recovery and improvement. Well-crafted and timely media releases are essential as primary information sources for the media, especially in crisis scenarios where prompt and precise information dissemination is critical. This method ensures that information, though disseminated quickly, maintains relevant and impactful storytelling aspects. The study concludes that storytelling, characterized by humanistic, empathetic, and coherent narratives across media statements, can be effectively utilized by Lion Air to uphold consistent and narrative-focused communication with the public through the media.